STRATEGY ANALYSIS IN PT. ENERGI INDONESIA MAJU AS A MANUFACTURER OF WASTE PELLETS FOR RENEWABLE ENERGY - Bonar Bastari, Ega; E. Sofyan, Rufyan; Hamdi, Edi; Yanuar Rahmat Syah, Tantri; Abadi, Ferryal (Jurnal Ilmiah Jendela Pendidikan, 2022)
People's need for energy tends to get higher from time to time. The energy that is needed is related to electricity. The current condition of power plants uses a lot of steam sources with the support of coal combustion. However, the coal owned will not last long because this source is non-renewable. For this reason, renewable energy sources are needed to overcome the scarcity of coal that will occur in the next few years. Waste pellets can be used to replace the role of coal for PLTU. For this reason, these waste pellets are produced by PT. Energi Indonesia Maju as a provider of waste pellets as a substitute for coal fuel. This journal aims to provide business considerations whether the production of waste pellets is able to develop and be profitable in the short and long term.